Positive RT-PCR Test Results in 420 Patients Recovered From COVID-19 in Wuhan: An Observational Study - He, Shaobin; Tian, Jiaxing; Li, Xiaodong; Zhou, Yana; Xiao, Mingzhong; Zhang, Ying; Min, Xiaojun; Li, Xiuyang; Jin, De; Zhang, Qing; Zheng, Yujiao; Ke, Jia; et al. (Frontiers in Pharmacology, 2020)
Objective: During the follow-up of patients recovered from coronavirus disease 2019 (COVID-19) in the quarantine and observation period, some of the cured patients showed positive results again. The recurrent positive RT-PCR test results drew widespread concern. We observed a certain number of cured COVID-19 patients with positive RT-PCR test results, and try to analyze the factors that caused the phenomenon. Methods: We conducted an observational study in COVID-19 patients discharged from 6 rehabilitation stations in Wuhan, China. All observed subjects met the criteria for hospital discharge and were in quarantine. Data regarding age, sex, body mass index (BMI), course of disease, comorbidity, smoking status and alcohol consumption, symptoms in and out of quarantine, and intervention were collected from the subjects’ medical records and descriptively analyzed. The main outcome of this study was the RT-PCR test result of the observed subjects at the end of quarantine (negative or positive). Logistic regression analysis was used to identify the influencing factors related to recurrent positive RT-PCR test results. Results: In this observational study, 420 observed subjects recovered from COVID-19 were included. The median age was 56 years, 63.6% of the subjects were above 50 years old, 50.7% (213/420) were female. The most common comorbidities were hypertension [26.4% (111/420)], hyperlipidemia [10.7% (45/420)] and diabetes [10.5% (44/420)]. 54.8% (230/420) manifested one or more symptoms at the beginning of the observation period, the most common symptoms were cough [27.6% (116/420)], shortness of breath 23.8% (100/420)] and fatigue [16.2% (68/420)], fever [2.6% (11/420)] was rare. A total of 325 subjects were exposed to comprehensive intervention; 95 subjects were absence of intervention. The recurrence rate of positive RT-PCR test results with comprehensive intervention was 2.8 % (9/325), and that with no intervention was 15.8% (15/95). The results of logistic regression analysis showed that after adjusted for factors such as age, sex and comorbidity, and found out that comprehensive intervention was correlated with the recurrent positive RT-PCR test results. Conclusions: The factors related to positive RT-PCR test results in observed subjects recovered from COVID-19 were age, comorbidity and comprehensive intervention, among which comprehensive intervention might be a protective factor.